Invisible light the remarkable story of radiology - Thomas, Adrian L. R. (CRC Press, Taylor & Francis Group, 2022)
The book is a developed history of the radiological sciences – covering the back-story to Röntgen’s discovery, the discovery itself and immediate reception the early days of radiology leading to classical radiology (the pre-digital world). The 1970s as the ‘golden decade’ of radiology will be covered in detail, with the development of CT, MRI and modern interventional radiology. It will appeal to interested members of the public, to those working in the field, and to historians of medicine and science